For my enemies, the law: Corruption as an argument to activate mechanisms of political control in Peru (2016-2020) - Carbajal, Álvaro (2024)
Corruption is a phenomenon deeply rooted in Peruvian republican history. Since the viceregal era, corruption scandals in the public apparatus have been recurrent. However, starting in the second half of the 2010s, when the international scandal known as “Lava Jato” was uncovered (from which Peruvian politics could not escape), corruption began to be used as an argument that triggered several presidential crises in Peru. Thus, various political control mechanisms, both in the Executive and the Legislative, were based on the fight against corruption to attack the rival power. In that sense, based on the qualitative analysis of the various documents presented, the arguments from both the Executive and Legislative Branches will be analyzed. These documents will be analyzed from the website of the Congress of the Republic of Peru. Finally, it is observed that corruption was used recurrently as an argument to delegitimize a State power in the midst of the fight between the government and Congress.